INDUKSI TUNAS JERUK SIAM DENGAN PENAMBAHAN BENZIL AMINO PURINE (BAP) SECARA IN VITRO - Yulianti Rasud; Hairil Anwar (Jurnal Agrotech, 2019)
The aims of this experiments was to evaluate the appropriate concentration of BAP for shoots induction of orange via in vitro culture. This experiment was conducted in Plant Biotechnology Laboratory, Faculty of Agriculture, Tadulako University from Mei to August 2017. This experiment used a Completely Randomized Design with five treatments, namely 0.5 ppm BAP, 1.0 ppm BAP, 1.5 ppm BAP, 2.0 ppm and 2.5 ppm.. Data was analyzed using analysis of variance and differences between means of the treatments were determined by Honestly Significant Difference test at 5% level. Results of this experiment indicated that the most suitable concentration of BAP for the shoots induction of orange was the medium culture supplemented with 0.5 ppm BAP. In such medium composition, the quickest and the highest number of shoot formation was obtained as well as the highest number of leaf formation at 6 weeks after culture, namely 3.02 days after culture, 1.52 shoots and 2.40 leaves per explant, respectively.